PENGEMBANGAN MEDIA POP UP BOOK SAINS PADA MATERI KENAMPAKAN PERMUKAAN BUMI SEKOLAH DASAR - Renny Fitria; M. Jaya Adi Putra; Eva Astuti Mulyani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The use of learning media in the teaching and learning process can generate new desires and interests, generate motivation and stimulate student learning activities. The use of learning media in the form of a pop-up book of science is one of the efforts so that students know semi-concrete shapes or images, especially on the material appearance of the earth's surface. With learning media in the form of 3 dimensions will help students' understanding and abilities. The average percentage gain from media expert validators is 94.58% and material expert validators are 95.83% with very decent criteria. For the teacher response test, the average percentage was 98.33% and the student response test was 97.40% with very decent criteria.Key Words: Science Pop Up Book Media, Earth’s Surface Appearance